ESP Need Analysis For Public Health Course Material: A Learner Centered Approach - Dania, Haris; Wirahmi Bay, Indri; Louise Sambouw, Elsje (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The purpose of this research is basically oriented towards the output of teaching materials based on English for Specific Purposes (ESP) modified learner-centered approach for Public Health sophomores, Faculty of Health and Sport, State University of Gorontalo. This research was conducted at the Faculty of Health and Sport (FOK) State University of Gorontalo, particularly in the Department of Public Health. The research was carried out for 2 years (2022-2023). This research is classified into the type of research development ( Research and Development or R & D) , which is a research that is used to produce certain products, and test the effectiveness of these products. The result showed that target need analysis covered the respondents considered the learnercentered approach to be practical and easy to understand in their learning (47.6%). However, complaints can occur because the learning process takes a long time with a percentage (64.3%). Therefore, researchers assume that these obstacles occur because learning strategies are still conventional, and the learning media used are not up to date. The possibility that occurs in learning is if the learning strategy is only centered on the teacher explaining the material without considering student knowledge. In Learning need analysis, Subindicators of public health topic covered some materials such as medication and treatment, ecosystem, pain, health environment, and monitoring the patients. For the learning activities, it refers to the demonstration as the indicator that is needed to be conducted. Then, the trouble undrstanding lecturing in ESP course is relevant with lecturing. Therefore, it seems clearly that the learning needs of Public Health students deals with the concept of speaking skill in learning process.